The Effect of Methanolic Extract of Manggarsih Stem (Parameria laevigata) into the Weight of Mice’s Testicles (Mus musculus) Swiss Strain - Almira Ulimaz (Universitas Sebelas Maret, 2015)
The research was conducted to determine the effect of methanolic extract of manggarsih stem (Parameria laevigata) into the weight of mice’s testicles. The research was carried out by giving methanolic extract of manggarsih stem to Swiss white mice orally, each mice was force-fed 0,5 milliliter / 25–30 g for 35 days with 5 treatments, namely P0 (control with distilled water), P1 (concentration of 5%), P2 (concentration of 10%), P3 (concentration of 15%), P4 (concentration of 20%), and four times repetition. In the day of 36th the mice was dissected to take the testicles, then the testicles weight was measured above analytical balance. Data were analyzed by normality test of Kolmogorov Smirnov, Homogenity test, Analysis of Variance test, and Duncan test. The results showed that parameter of testicles weight was not significant (sig < 0,05). It is concluded that methanolic extract of manggarsih stem can not decrease the mean number of testicles weight.Keywords: manggarsih stem (P. laevigata), methanolic extract, weight of mice’s testicles